Analysis of jurisprudence related to the asbesto’s case in Chile and the violation of fundamental rights of victims - Suárez Donaire, Leticia; Malebrán Guerra, Edgar (Derecho Público Iberoamericano, 2023)
The asbesto has been identified as a material that causes various damages to both human health and the environment, for which reason national and international law has prohibited its use, notwithstanding which in Chile it has continued to be used under certain exceptions, with the consequent damages that derive from it, which has led to the filing of numerous claims for compensation for damages, many of which have concluded by way of conciliation and compromise. Faced with this, the present work invites us to reflect on the availability of compensation for violation of fundamental rights, and the effectiveness of leaving its safeguard only to the courts of justice.